ROSTYSLAV SERGIYOVYCH FURDUY – ENTHUSIAST OF THE GEOLOGICAL WORK - Gryshchuk, P.; Vakulenko, O.; Kozionova, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article discusses production, scientific, educational and museum activities of the Cand. Sci. (Geol.-Min.) Rostislav Sergeevich Furduy, most of which are closely related to the geological faculty of the University of Kiev. The authors are used both their personal relation experience as well as materials about R.S. Furduy that describe his life activities in various areas his personal preferences and hobbies. The article describes educational, scientific and creative nature of Rostislav Furduy including unique improvements made by him for Geological Museum during 20022012 years. Main stages of R.S. Furduy’s life as well as use full educational and scientific contribution share as made by such an outstanding person during his work at the geological faculty of the Taras Shevchenko National University of Kyiv are analyzed.